Meningococcal serogroup B vaccine: Knowledge and acceptability among parents in Italy - Teresa Morrone; Francesco Napolitano; Luciana Albano; Gabriella Di Giuseppe (Taylor & Francis Group, 2017)
This study aimed to evaluate the knowledge and attitudes about Meningococcal meningitis B and the relative vaccine for children among a sample of parents in Italy. A cross-sectional investigation was conducted from October to December 2015 among a sample of 910 parents in the geographic area of Naples and Salerno (Italy). In total, 543 of 910 parents returned a completed questionnaire for a response rate of 59.7%. Almost all parents had heard about meningitis (95.8%), 79.8% of these knew the mode of transmission (through respiratory droplets) and 62.5% knew the susceptible population (infants, children and adolescents). Moreover, a large percentage (86%) knew that the vaccine is a preventive measure. Parents who were married, those who had one child, those who did not have information about the MenB vaccine by physicians and those who needed additional information about the MenB vaccine were more likely to know the vaccine as a preventive measure of meningitis. Regarding attitudes toward the MenB vaccine, approximately two thirds of parents considered the vaccine useful (67.2%) and said that they would vaccinate their children (64.1%). Parents who had administered at least one recommended vaccination to their children, those who considered the vaccine useful, those with need for additional information about the vaccine and those who knew that the vaccine was a preventive measure of meningitis were more likely to have a positive attitude to vaccinating their children. Considering the results of our study, it looks appropriate that the knowledge of the population about meningitis and its related vaccinations is improved through correct health education and effective vaccine strategies that are implemented by policy makers.